(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
This article provides a scientific and theoretical analysis of the process of globalization and its impact on intercultural communication. The economic, political, and cultural aspects of globalization are examined, and the modern forms, opportunities, and challenges of intercultural communication are highlighted. The article also discusses issues such as preserving national identity, developing cultural diversity, and effectively organizing cultural dialogue in the context of global integration.